2022
DOI: 10.3389/fmicb.2022.1039614
|View full text |Cite
|
Sign up to set email alerts
|

Circulating soluble CD36 as a novel biomarker for progression and prognosis of HBV-related liver diseases

Abstract: BackgroundOur previous study suggested CD36 may be a positive regulator of hepatitis B virus (HBV) replication in vitro. Therefore, the present study aimed to investigate whether circulating soluble CD36 (sCD36) could serve as a diagnostic and prognostic biomarker for HBV-related liver diseases based on the clinic collected data.MethodsA total of 282 subjects were divided into healthy controls (HC, n = 47), chronic hepatitis B (CHB, n = 68), HBV-related liver cirrhosis (HBV-LC, n = 167). Soluble CD36 in plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In a cohort study, the levels of soluble CD36, an indicative marker for macrophage lipid accumulation, were measured (112). The findings revealed elevated levels of soluble CD36 in individuals with impaired glucose regulation, metabolic syndrome, and an increased likelihood of fatty liver, as determined by noninvasive steatosis estimates (113,114). Moreover, several studies have reported sCD163, a macrophage activation marker specific to certain lineages, as a promising biomarker for predicting liver disease severity (115)(116)(117)(118)(119).…”
Section: Macrophage Biomarkersmentioning
confidence: 99%
“…In a cohort study, the levels of soluble CD36, an indicative marker for macrophage lipid accumulation, were measured (112). The findings revealed elevated levels of soluble CD36 in individuals with impaired glucose regulation, metabolic syndrome, and an increased likelihood of fatty liver, as determined by noninvasive steatosis estimates (113,114). Moreover, several studies have reported sCD163, a macrophage activation marker specific to certain lineages, as a promising biomarker for predicting liver disease severity (115)(116)(117)(118)(119).…”
Section: Macrophage Biomarkersmentioning
confidence: 99%